Recycled PET Plastics Filament: Characteristic and Cost Opportunity - Putra, Ikbal Rizki; Bukhori, Muhammad Luqman; Prasetiyo, Angger Bagus; Robbika, Fadzkurisma; Putra, Brian Teo (Semesta Teknika, 2024)
Piyungan Integrated Waste Disposal Site (TPST) is a waste disposal site in Yogyakarta province. With an estimated increase in the amount of waste of 8% per year, it is estimated that the TPST will not be able to accommodate waste from the community. One of these wastes is PET bottle. This research aims to develop a new recycling method by converting PET plastic waste into 3D Printer machine filament and investigate the opportunity of this PET filament. This research uses several stage methods: PET filament making, Tensile test, macroscopy photography and opportunity analysis. This study concludes that PET bottle waste can be used as 3D printer filament with a diameter of 1.7 mm. Processing PET bottle waste into 3D printer machine filament can increase the economic value of PET bottle waste. And this can contribute to the potential for processing plastic bottle waste.